2013
DOI: 10.1016/j.jenvman.2013.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of a high-speed railway line on species distribution: Application to the European tree frog (Hyla arborea) in Franche-Comté

Abstract: The aim of the present work is to assess the potential long-distance effect of a high-speed railway line on the distribution of the European tree frog (Hyla arborea) in eastern France by combining graph-based analysis and species distribution models. This combination is a way to integrate patch-level connectivity metrics on different scales into a predictive model. The approach used is put in place before the construction of the infrastructure and allows areas potentially affected by isolation to be mapped. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 59 publications
1
36
0
2
Order By: Relevance
“…For these purposes, graph theory is being increasingly used in conservation biology, as graph models provide simplified representations of ecological networks with flexible data requirements (Urban et al 2009). For instance, Clauzel et al (2013) (see also Chap. 13) combined graph-based analysis and species distribution models to assess the impact of a railway line on the future distribution of the European tree frogs (Hyla arborea) in France.…”
Section: Indirect Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For these purposes, graph theory is being increasingly used in conservation biology, as graph models provide simplified representations of ecological networks with flexible data requirements (Urban et al 2009). For instance, Clauzel et al (2013) (see also Chap. 13) combined graph-based analysis and species distribution models to assess the impact of a railway line on the future distribution of the European tree frogs (Hyla arborea) in France.…”
Section: Indirect Methodsmentioning
confidence: 99%
“…Impacts can be predicted by NGS (Balkenhol and Waits 2009) or by censuses (Species Distribution Models, Clauzel et al 2013). In addition, individual assignment tests and graph theory could be combined in landscape analyses to identify connectivity zones that should be preserved, and computer simulations could be run to evaluate population dynamics under several barrier effect levels (Balkenhol and Waits 2009;Clauzel et al 2013).…”
Section: Forecasting Impactsmentioning
confidence: 99%
“…Finally, the cores of forest patches, bare ground, buildings and motorways are considered highly impassable and are mostly avoided by the tree frog. Clauzel et al (2013) performed several tests by varying the cost values and the number of classes to find the model that best explained the occurrence of the tree frog in the Franche-Comté region. The results showed that highly contrasting values between favorable and unfavorable landscape categories were the most relevant.…”
Section: Landscape Graph Constructionmentioning
confidence: 99%
“…From the two landscape maps, without and with the HSR line, two graphs were built and thresholded at a distance of 2500 m corresponding approximately to the dispersal distance for the tree frog. This distance was selected in line with the results by Clauzel et al (2013), where several maximum distances were tested. The model using the distance of 2500 m proved the most relevant.…”
Section: Landscape Graph Constructionmentioning
confidence: 99%
“…More recently, the protection of the habitats crossed by railways and their wildlife has become a main factor to be taken into consideration when designing new railways or maintaining existing ones (Clauzel et al 2013;Profillidis 2014), associated with an increased societal awareness of the importance of biodiversity (Pereira et al 2012). However, compared to other transportation systems, such as roads, less is known about the impact of railways on wildlife, as well as its specificities.…”
Section: Introductionmentioning
confidence: 99%